IMPLEMENTASI METODE QIRO’ATI DALAM MENINGKATKAN KELANCARAN MEMBACA AL-QUR’AN - Makhrus Ali, M.; Robbaniyah, Atiyatur; Mahendra Datta , Dicky (As-Sulthan Journal of Education, 2025)
This study examines the implementation of the Qiro'ati method to improve Quranic recitation fluency at the Jam'iyatul Qurro' Quranic Education Center (TPQ). In the context of Islamic religious education, TPQ plays a vital role in shaping the character, morality, and Quranic reading skills of its students. The focus of this study is to understand how the Qiro'ati method is adopted and implemented at TPQ and its impact on students' Quranic reading skills. This study uses an action approach with a cycle of planning, action, observation, and reflection. The research location is TPQ Jam'iyatul Qurro' in Pengumben Hamlet, Probolinggo Regency, East Java. Data collection methods include observation, interviews, and documentation. The research findings cover the history, identity, flagship programs, vision, mission, learning media, and learning processes at TPQ. Through learning innovation and a holistic approach, TPQ Jam'iyatul Qurro' is committed to creating a learning environment that supports the spiritual, social, and academic development of students. The results of this study are expected to contribute to the scientific literature on Islamic religious education and Quranic learning methods.